Penerapan Metode Pembelajaran Role Playing Berbantuan Video Pembelajaran untuk Meningkatkan Pemahaman Konsep IPS pada Siswa Kelas V Sekolah Dasar - Sri Setik Nurhamami (Journal on Education, 2021)
The purpose of this study was to describe the improvement of the social studies concept of the fifth grade students of SDN Wonokusumo VI / 45 Surabaya by using the role playing method. This research was conducted using the Classroom Action Research (CAR) method with the research model design of Kemmis and Mc. Taggart. The research was conducted in 3 cycles. The research subjects were students of class V SDN Wonokusumo VI / 45, which may be 32 students. Collecting data using observation techniques, learning outcomes (understanding concepts) and documentation. The data from the observations are in the form of observations of teacher activities with role playing methods and observations of student activities in learning. The concept test of understanding the cognitive aspects of learning outcomes tests which is the final evaluation exercise of each cycle to measure the assessment of social studies learning by applying the video-assisted role playing method. The results showed that the use of the video-assisted role playing method could improve students' conceptual understanding as indicated by the acquisition of the average value and the proportion of classical submission from cycle I to cycle II. Students' understanding of the concept in the first cycle showed an average value of 62.50 with the classical classification proportion of 21.80% with the poor category. In the second cycle it increased to 70.94 with a classical proportion of 53.13% in the sufficient category. The average cycle III student scores increased 76.56 percent from classical 81.25% with very good category. Keywords: Role Playing, Learning Videos, Concept Understanding.